2017
DOI: 10.1177/1053451217712974
|View full text |Cite
|
Sign up to set email alerts
|

Using Lesson Study to Prepare Preservice Special Educators

Abstract: Learning to teach students with disabilities is challenging. Preservice special educators must develop critical knowledge of content as well as skill for enacting evidence-based practices effectively. Preservice special educators need increased opportunities to learn core knowledge coupled with a mechanism to support them in situating their newly acquired knowledge and skills in classroom practice. This column describes lesson study (LS), a practice-based approach that can be integrated within a teacher prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Through LS, teachers will work collaboratively to reach the shared goals set ahead, which they think are necessary to develop competencies for their students. However, less theoretical work explains how teachers learn in the LS context and how LS contributes to and supports teacher learning (Dudley 2015;Elliott 2012) Roberts et al (2017) found that preparation is vital in conducting LS. The preservice teachers should use critical content knowledge and establish lesson study teams and tools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through LS, teachers will work collaboratively to reach the shared goals set ahead, which they think are necessary to develop competencies for their students. However, less theoretical work explains how teachers learn in the LS context and how LS contributes to and supports teacher learning (Dudley 2015;Elliott 2012) Roberts et al (2017) found that preparation is vital in conducting LS. The preservice teachers should use critical content knowledge and establish lesson study teams and tools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because lesson study is conducted in tutoring or classroom settings, it affords a well-structured, authentic practice opportunity. In addition, the collaborative nature of this approach helps teacher candidates prepare for their first teaching positions, as they learn to work closely with colleagues to collaboratively analyze and discuss student data, curriculum, and plan and teach instruction in coordinated efforts (Roberts, Benedict, Kim, & Tandy, 2018). Implementing lesson study, however, requires considerable time and coordination on the part of faculty.…”
Section: Analysis Of Practice-based Opportunitiesmentioning
confidence: 99%
“…Teachers with a variety of expertise and experience have benefitted from collaborating in Lesson Study programs. For example, pre-service (Roberts, Benedict, Kim, & Tandy, 2017;Sims & Walsh, 2009), elementary (Cheung, 2011;Gutierez, 2016), middle (Lieberman, 2009), and high school (Cajkler, et al, 2015) teachers have developed professionally; so too have college instructors (Dotger, 2011). Scholars have used Lesson Study to investigate contexts where teachers have taught students Math (Leavy & Hourigan, 2016), Science (Lewis & Tsuchida, 1997), English (Nami, Marandi, & Sotoudehnama, 2016), Modern Languages (Cajkler & Wood, 2016), and social studies (Halvorsen & Kesler Lund, 2013;Marton & Pang, 2006;Matoba et al, 2007).…”
Section: Lesson Study Collaborationmentioning
confidence: 99%